Fam65b Phosphorylation Relieves Tonic RhoA Inhibition During T Cell Migration - Megrelis, Laura; El Ghoul, Elyas; Moalli, Federica; Versapuech, Margaux; Cassim, Shamir; Ruef, Nora; Stein, Jens V.; Mangeney, Marianne; Delon, Jérôme (Frontiers in Immunology, 2018)
We previously identified Fam65b as an atypical inhibitor of the small G protein RhoA. Using a conditional model of a Fam65b-deficient mouse, we first show that Fam65b restricts spontaneous RhoA activation in resting T lymphocytes and regulates intranodal T cell migration in vivo. We next aimed at understanding, at the molecular level, how the brake that Fam65b exerts on RhoA can be relieved upon signaling to allow RhoA activation. Here, we show that chemokine stimulation phosphorylates Fam65b in T lymphocytes. This post-translational modification decreases the affinity of Fam65b for RhoA and favors Fam65b shuttling from the plasma membrane to the cytosol. Functionally, we show that the degree of Fam65b phosphorylation controls some cytoskeletal alterations downstream active RhoA such as actin polymerization, as well as T cell migration in vitro. Altogether, our results show that Fam65b expression and phosphorylation can finely tune the amount of active RhoA in order to favor optimal T lymphocyte motility.